Entrepreneurial Leadership: A New Paradigm, Context, and Vision of Effective Leadership with Women Emerging as Successful Entrepreneurs - Jha, Sneha (Digital Repository of Theses - SSBM Geneva, 2024)
The development of visible light on the " Entrepreneurial Leadership: A new paradigm, context and vision of effective leadership with women emerging as successful entrepreneurs”. The study evaluated the relationship between women entrepreneurs' success and entrepreneurial leadership. The study investigates the relationship between women entrepreneurs' success in India and their leadership in entrepreneurship. The target market is Indian women entrepreneurs who successfully manage their businesses. The study's goals are to investigate the impact of leadership on the success of entrepreneurs, evaluate motivating variables, investigate women's entrepreneurial potential, and identify obstacles that stand in the way of women's entrepreneurial success. A descriptive research design was used in the study. To do a thorough statistical analysis, the study established commercial statistical tools like Excel and SPSS. There were many different statistical approaches to take into account for this study; nevertheless, the ones that were chosen were regression analysis, analysis of variance (ANOVA), correlation analysis, and mean and standard deviation, depending on the objectives and hypotheses of the research. The purpose of the study is to shed light on the dynamics of entrepreneurial leadership and how they affect the success of women in business. By identifying the particular possibilities and constraints encountered by women entrepreneurs, the research adds to our knowledge of the dynamic environment of entrepreneurial leadership. This study promotes gender inclusion in entrepreneurship and challenges cultural assumptions to assist the development of enabling settings that enable women's economic empowerment and creativity.